CLASS-BASED DEATH: COVID-19 AMONG THE ELDERLY PEOPLE IN NIGERIA - Abdullahi Muhammad Maigari (Indonesian Journal of Sociology, Education, and Development, 2021)
The article examined the nature of deaths related to COVID-19 complications in Nigeria based on age. The researcher observes that National Centre for Disease Control, responsible for handling COVID-19 and reporting daily cases, only provides crude data about active, confirmed cases and deaths without grouping the data based on demographic characteristics. This motivated the researcher to sample some people who died as a result of the COVID-19 to carry out an age-specific analysis. Fifteen elderly people whose death was attributed to COVID-19 were sampled. To achieve the purpose of the study, secondary data were sourced, presented, interpreted, and analysed in a tabular form. The study found that there is a paucity of COVID-19 data that reveals the sociodemographic characteristics of either affected persons or those who died. Similarly, the paper established most of the elderly people who died as a result of the COVID-19 were at the top echelon of social class.